Analysis of the Role of Teacher Learning Community in Improving Pedagogic Competence and Teacher Professionalism in Labuhanbatu Secondary School - Darajat, Mulkan; Sipahutar, Yunita; Batubara, Monica Mulyani; Febriani, Budi; Lubis, Leli Hasanah (Edumaspul: Jurnal Pendidikan, 2024)
This study aims to analyze the role of Teacher Learning Communities (TLC) in enhancing pedagogical competence and teacher professionalism in secondary schools in Labuhanbatu Regency, North Sumatra. The research employs a descriptive qualitative approach, using data collection methods such as in-depth interviews, direct observation, and document analysis. The findings reveal that TLCs play a significant role in assisting teachers in developing creative teaching strategies, improving classroom management skills, and expanding educational technology literacy. Additionally, TLCs encourage the development of teacher professionalism by increasing engagement in training and ongoing professional activities. Despite challenges such as time constraints and varying participation levels, structural support from schools, particularly in time management and motivation, is crucial to ensuring the sustainability and effectiveness of TLCs. This study concludes that TLCs hold great potential as a sustainable teacher professional development model, positively impacting the future quality of education.